2002
DOI: 10.1093/nar/gkf392
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial DNA polymerase as a target of oxidative damage

Abstract: The mitochondrial respiratory chain is a source of reactive oxygen species (ROS) that are responsible for oxidative modification of biomolecules, including proteins. Due to its association with mitochondrial DNA, DNA polymerase gamma (pol gamma) is in an environment to be oxidized by hydrogen peroxide and hydroxyl radicals that may be generated in the presence of iron ions associated with DNA. We tested whether human pol gamma was a possible target of ROS with H2O2 and investigated the effect on the polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 41 publications
5
100
0
3
Order By: Relevance
“…For example, Graziewicz et al (18) showed that the human ␥-polymerase, the only polymerase present and active in mitochondria, is prone to oxidative damage. This might also be the case in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Graziewicz et al (18) showed that the human ␥-polymerase, the only polymerase present and active in mitochondria, is prone to oxidative damage. This might also be the case in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that concentrations ranging from 50 to 150 M promote DNA damage (9,10) replicative senescence (11)(12)(13), sustained p21 levels, cell cycle arrest, transient elevation of p53 protein (14), and temporary growth arrest followed by increased resistance to subsequent oxidative stress (8,15). In contrast, H 2 O 2 doses of 200 M and higher were demonstrated to induce apoptosis (16), necrosis (16,17), protein oxidation (18), as well as lesions in both nuclear and mitochondrial genomes (9,10).…”
mentioning
confidence: 99%
“…18 In functional studies, exposure to hydrogen peroxide, a reactive oxygen species, resulted in damage to the DNA replication enzyme (polymerase g) in the mitochondria and a reduction in mtDNA copy number. 19,20 Exposure to TNF-a, an inflammatory cytokine, also generated reactive oxygen species and reduced mtDNA copy number in myocytes. 21 Cross-sectional studies of patients with CKD have shown that lower mitochondrial function, indicated by metabolites from urine and gene expression from peripheral blood, correlated with more severe CKD.…”
Section: Main Findingsmentioning
confidence: 99%
“…Nuclear genes include those encoding the adenine nucleotide translocator 1 (2), thymidine phosphorylase (3), mitochondrial DNA helicase (Twinkle) (4), and the catalytic subunit of mitochondrial DNA polymerase (pol 1 ␥) (5). Pol ␥ has also been shown to be a target of oxidative damage, which reduces DNA polymerase activity in the mitochondrial matrix (6).…”
mentioning
confidence: 99%